BO‘LAJAK MUSIQA O‘QITUVSHILARINING PEDAGOGIK FAOLIYATGA TAYYORLASHDA IJODIY QOBILIYATLARNI SHAKLLANTIRISHNING MUHIM JIHATLARI - Davronova, G.M. (SCIENCE and SOCIETY, 2023)
In this article, the important pedagogical and methodical aspects of the formation of creative abilities are highlighted in the preparation of future music education teachers for professional activities at the level of modern requirements.